Domestic Politics, Foreign Policy, and International Organization: The Case of Indonesia’s Withdrawal from the United Nations - Yohanes Sulaiman (Universitas Jenderal Ahmad Yani, 2018)
Under what condition states will withdraw from an international organization? This article examines this question from the perspective of three systemic approaches: realism, liberalism, and constructivism by generating hypotheses from each approach and testing them on the case of Indonesia's withdrawal from the United Nations in 1965. The systemic perspectives, however, could only provide partial answers to this puzzle, and thus the need to include domestic political analysis in conjunction of the systemic analysis in order to fully answer the question.